The Role of the International Financial Reporting Standards in Enhancing the Quality of Sustainable Accounting Information - Anmar Adnan Khudhair (Harmoni Economics: International Journal of Economics and Accounting, 2025)
Purpose: The research examines the relationship between international financial reporting standards and   sustainability accounting information. International financial reporting could affect the efficiency and effectiveness of accounting information disclosure by transparency financial reports. Design/methodology/approach: This research collects the data by using the questionnaire technique distributed to accountants and auditors in trade companies and financial analysts in financial brokerage companies. The Mann-Whitney test is applied to examine the hypotheses of this study model. Findings: This research finds that the application of international financial reporting standards positively impacts the efficiency and effectiveness of sustainability accounting information. Thus, international financial reporting standards have many advantages and positive impacts regarding the necessity of their application in business companies. Originality/value: Although many studies have investigated sustainability accounting, no research has addressed the association between international financial reporting standards and the efficiency and effectiveness of accounting disclosure in financial reports in emerging markets in Iraq. In addition, this research shows the importance of the efficiency and effectiveness of quality accounting information in company reports to inspire companies to provide financial reports with a high level of transparency. Also, the results offer valuable insight into improving the quality of financial reports and accounting information's to attract foreign investors. The five-point Likert scale was used to express the totality of the five dimensions, in which the measurements range from one point with a strongly disagree content to five points with a strongly agree content, in addition to the program ((spss), and (159) questionnaires were distributed to several employees. The research sample of companies listed in the Iraq Stock Exchange and its analysis using multiple statistical techniques.